High-throughput analysis using 16S rRNA gene of bacterial communities present in selected bivalves and gastropods species from Bayug Island, Iligan City, Philippines - NITCEL AYMIE ALBARIDO; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Albarido NA, Tabugo SR. 2024. High-throughput analysis using 16S rRNA gene of bacterial communities present in selected bivalves and gastropods species from Bayug Island, Iligan City, Philippines. Biodiversitas 25: 431-438. Seashells, which include bivalves and gastropods, have global recognition for their significant contributions to the economy, ecology, and medicine. They hold value as a food source and are highly regarded as effective biological indicators. The objective of this study is to identify the bacterial communities present in selected edible species of bivalves (Pinctada margaritifera Linnaeus, 1758 and Anadara granosa Linnaeus, 1758) and gastropods (Canarium urceus Linnaeus, 1758 and Conus stercusmuscarum Linnaeus, 1758), through high-throughput sequencing metabarcoding. Bacterial samples were collected via a swabbing technique on the surface and inside parts of selected mollusc species, which were then placed on sterilized seawater for DNA extraction. Genomic DNA was isolated from the samples, and the V3-V4 region of the 16S rRNA gene was amplified and sequenced using the Illumina MiSeq platform. Four amplicon libraries were generated, representing the two bivalve and two gastropod species in the study area. Data analysis was conducted using the Parallel Meta Suite software. Upon quality control and processing, 173,489 amplicon sequence variants (ASVs) were obtained. Within the bacterial community, the most abundant genera included Stenotrophomonas, Vibrio, Serratia, Photobacterium, and Shewanella. The assessment of alpha diversity, using the Shannon index, indicated a higher diversity in A. granosa. Furthermore, the analysis using the PICRUSt algorithm within the Parallel Meta Suite unveiled the involvement of specific bacteria found in the selected gastropod and bivalve species in various functions. These functions encompass protein production, xenobiotic metabolism, biodegradation, and other metabolism-related processes, supporting these organisms' ecological and physiological roles.